Using design science to improve web search innovation in real estate. Issue 3 (2nd July 2016) - Grant, Delvin; Cherif, Emna
ABSTRACT: We analyze 14 leading real estate websites, seven residential and seven commercial. They exhibit limited demographic and geographic information systems (GIS) data display capability. They exhibit economic data display capability except one, and lack demographic, economic, and GIS data search capability. Real estate web searching is inefficient, time consuming, and inflexible. To overcome these limitations, we use design-science to create three search modes (Sc2, Sc3, and Sc4). Sc2 uses demographic data, Sc3 economic data, and Sc4 GIS data.